Labor market prospects, search intensity and the transition from college to work - Bas van der Klaauw; Aico van Vuuren; Peter Berkhout (Institute for Labour Market Policy Evaluation (IFAU), 2005)
In this paper we develop a structural model for job search behavior of students entering the labor market. The model includes endogenous search effort and on the job search. Since students usually do not start a regular job before graduation but start job search earlier, our model is not stationary. The model explains the common finding that a substantial share of individuals starts working immediately upon graduation. We estimate the model using a unique data set of individuals who completed undergraduate education in the Netherlands between 1995 and 2001. Our estimation results show that 1 percentage point decrease in unemployment rate increases wage offers on average with 3 percent and that there are substantial returns to work experience. Employment rates at graduation could be increased from 40 percent to 65 percent if alls students start job search 6 months prior to graduation.
Keywords: J64; 330; Job search behavior; structural model; Akademiker; Arbeitsuche; Bildungsertrag; Konjunktur; Schätzung; Schätzung; Niederlande; Berufseinstieg